2015
DOI: 10.1159/000371600
|View full text |Cite
|
Sign up to set email alerts
|

Two New Cases of 1p21.3 Deletions and an Unbalanced Translocation t(8;12) among Individuals with Syndromic Obesity

Abstract: due to duplication of the GNB3 gene. Thus, our findings add to the existing literature on the clinical description of these new syndromes, providing additional support that these loci are associated with syndromic obesity. We suggest that heterozygous loss of MIR137 may contribute to obesity as well as ID and ASD. AbstractObesity is a highly heritable but genetically heterogeneous disorder. Various well-known microdeletion syndromes (e.g. 1p36, 2q37, 6q16, 9q34, 17p11.2) can cause this phenotype along with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Twelve patients carrying 1p21.3 deletions have been described in the literature to date [36], presenting with mild to moderate ID (100 %), obesity or a tendency to obesity, with a weight 3 or more standard deviations above the mean (92 %), ASD (92 %) and mild dysmorphic features (67 %) (Fig. 1 and Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve patients carrying 1p21.3 deletions have been described in the literature to date [36], presenting with mild to moderate ID (100 %), obesity or a tendency to obesity, with a weight 3 or more standard deviations above the mean (92 %), ASD (92 %) and mild dysmorphic features (67 %) (Fig. 1 and Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The minimal overlapping region was restricted to a chromosomal segment of 1.22 Mb, which includes the DPYD and MIR137 genes. DPYD was proposed as the gene contributing to the phenotype [3, 5], based on the assumption that its haploinsufficiency would contribute to the development of a neuropsychiatric phenotype, which also leads to obesity. However, the case herein presented and the patient recently reported by Pinto et al [6] carried a deletion overlapping in the critical region only at the MIR137 , which suggests that this is the gene underlying the phenotype of patients carrying deletions at 1p21.3.
Fig.
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we showed that genomic deletions affecting DPYD occurred in 7% of pediatric patients with a complete DPD deficiency (van Kuilenburg et al., ). Genomic rearrangements in DPYD have also been observed in patients with ID (Willemsen et al., ), autism‐spectrum disorder (Carter et al., ; Prasad et al., ), syndromic obesity (D'Angelo, Moller Dos Santos, Alonso, & Koiffmann, ), and amyotrophic lateral sclerosis (Uyan et al., ). To date, no clear genotype–phenotype correlation has been established in patients with a DPD deficiency but it is noteworthy that patients with gross deletions in DPYD presented with a severe phenotype when compared with that observed in other DPD patients (van Kuilenburg et al., ).…”
Section: Genotype and Biochemical Phenotype Of A Family With Dpd Defimentioning
confidence: 97%
“…The following information on included studies was collected: first author, gene symbol, age of mice, analyzed brain region, test platform, database, and project number. With all above, the major clinical information related to these mutant genes was collected from OMIM database and several reviews [Carratala-Marco et al, 2018;D'Angelo, Moller, Alonso, & Koiffmann, 2015;Geets, Meuwissen, & Van Hul, 2019;Merner et al, 2016;Tucci, Ciaccio, Scuvera, Esposito, & Milani, 2016].…”
Section: Identification Of Literature and Collection Of Informationmentioning
confidence: 99%